The Effect of the Genially-Assisted Contextual Teaching and Learning Model on Social Studies Concept Understanding - Rizqa Mardhiah; Nurdiansyah; Tiara Yogiarni (Lembaga Bale Literasi, 2026)
This study was motivated by the low level of students’ understanding of social studies concepts in elementary school due to teacher-centered learning and the lack of interactive learning media. This study aimed to determine the effect of the Contextual Teaching and Learning model assisted by Genially on students’ understanding of social studies concepts and to compare the conceptual understanding of students taught using the Contextual Teaching and Learning model assisted by Genially with those taught using the Student Teams Achievement Divisions (STAD) model assisted by PowerPoint Canva. This study employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The sample consisted of 52 fourth-grade students divided into an experimental class and a control class. The research instrument used multiple-choice tests. Data collection techniques included tests and documentation. Data were analyzed using normality tests, homogeneity tests, t-tests, and N-Gain analysis. The results showed that the Contextual Teaching and Learning model assisted by Genially had a positive effect on improving students’ understanding of social studies concepts. Furthermore, students taught using the Contextual Teaching and Learning model assisted by Genially achieved better conceptual understanding compared to students taught using the Student Teams Achievement Divisions (STAD) model assisted by PowerPoint Canva. Therefore, the Contextual Teaching and Learning model assisted by Genially can be used as an innovative learning alternative to improve students’ conceptual understanding in elementary social studies learning.